(RE)THINKING HISTORY: WOMEN AND THE CONSTRUCTION OF A SOCIOLOGICAL KNOWLEDGE - Saraiva de Oliveira Neto, Edival (Revista Gênero e Interdisciplinaridade, 2022)
The present work aims to show the academic production of three great thinkers, Harriet Martineau (1802-1876), Flora Tristan (1803-1804) and Marianne Weber (1870-1954), erased from the history of the development of sociology as a scientific and who had considerable contributions in debating topics that are still of interest to sociologists and social scientists, such as the relationship between the researcher and the object, the female condition, neutrality of knowledge, religion, among others considered fundamental for the development of sociological knowledge. To achieve this objective, we will use bibliographies that help us to think about the questions posed by these thoughts, and their main research themes, as well as authors that help us to critically think about the formation of sociological thought, showing that its structuring is much broader than weigh only through the canons reveal to us.